8 - Environnement socio-culturel et sous représentativité des femmes dans les programmes de lutte contre le travail des enfants dans le secteur du cacao en Côte d’Ivoire. - Sangare, Moussa; Kam, Oleh (African Sociological Review, 2022)
Child labor is a known problem in the cocoa sector in Côte d’Ivoire with a high level of occurrence. This has led to initiatives by various actors (state actors, NGOs, populations) to reduce or even eradicate this phenomenon. However, certain social categories of women are generally underrepresented in these initiatives to combat child labor, because of several socio- cultural factors. So the aim of the study is to show that the socio-cultural environment of women influences their representativeness in cocoa marketing cooperatives and indirectly the fight against the worst forms of child labor. The evaluation used a participatory, consultative and inclusive approach using the literature review, stakeholder interviews at the national, regional and local levels, experience visits and focus groups at the community level. The study took place in the localities of: Guéyo (Soubré) in the region of Nawa, Daloa and Issia in the region of Haut Sassandra, Abengourou and Agnibilékrou in the region of Indénié in the East. For its development, this study relied on the qualitative approach for data consultation. For the consultation of the data, this qualitative approach favored the mode according to the reasoned choice sampling, which made it possible to question (200) people.The results of the study show, on the one hand, that women are under-represented in areas with high cocoa production because of the socio-cultural values of tradition. On the other hand, certification does not fully take into account the gender issue. Indeed, women do not enjoy the benefits of certification, including access to premiums paid to their husbands as part of certification.